Experimental study on burning behavior of crude oil pool fire in annular ice cavities. (15th December 2018) - Kong, Depeng; Zhang, Zhen; Ping, Ping; Chen, Guoming; He, Xu; Yang, Hanbing
Highlights: A series of oil pool fire experiments in annular ice cavities were conducted. Decrease of inner diameter is 1.1 times as much as increase of outer diameter. The burning rate exhibits initial growth, merged growth and decay stage. Fire merging has a significantly effect on the burning rate and flame height. A model for predicting the flame height is established. Abstract: A series of experiments with different pool sizes and moisture contents were conducted to study the combustion behavior of pool fires in annular ice cavity. The initial pool area of 78.5 cm 2 and the initial oil thickness of 10 mm were determined in the each experiment. The results show that the double lateral cavity is formed after the pool fire in an annular ice cavity and the decrease of inner diameter is about 1.1 times as much as increase of outer diameter. Compared with circular ice cavity pool fires, fire merging, a unique phenomenon in annular ice cavity pool fires, was observed. The burning rate exhibits three stages: initial growth stage, merged growth stage and decay stage. Increasing pool diameters and moisture contents reduce the burning rate and flame height. The merged intensity ( Im ) increases as the increase of pool diameters and moisture content, while the influence coefficient of merged fire ( φ ) has a contrary trend. A new correlation for predicting the flame height is proposed.